Strategi Pemerintah Desa Dalam Meningkatkan Partisipasi Masyarakat Terhadap Pembangunan Desa (Studi Kasus Di Bahal Kabupaten Padang Lawas Utara) - Apriliani, Susi; ., Imsari (CV. ITTC INDONESIA, 2023)
In development, community participation is one of the elements of the village development process so that community participation in development needs to be raised in advance by several parties including the village government so that with the involvement of the village government it is likely that the community will feel given the opportunity or opportunity to participate in development. The research objective is to find out the village government's strategy in increasing community participation in village development (Case Study in Bahal, North Padang Lawas Regency). This research uses the research method that the author does in this paper, namely by using qualitative methods. Research result. The level of community participation in Tarowang Village can be seen in the planning, implementation and monitoring stages which are classified as good in terms of community participation in the planning stage, the implementation stage of development and utilization and maintenance. Community participation increases because the awareness to build a village has been instilled from within them to contribute directly.